Kinetochore malfunction in human pathologies - de Wolf, Bas; Kops, Geert J.P.L. (Springer, 2017)
The cell cycle culminates in mitosis with the purpose of dividing the cell’s DNA content equally over two daughter cells. Error-free segregation relies on correct connections between chromosomes and spindle microtubules. Kinetochores are complex multi-protein assemblies that mediate these connections and are the platforms for attachment-error-correction and spindle assembly checkpoint signaling. Proper kinetochore function is therefore key in preventing aneuploidization. Mutations in genes encoding kinetochore proteins are associated with several severe developmental disorders associated with microcephaly, and kinetochore defects contribute to chromosomal instability in certain cancers. This chapter gives an overview of the processes necessary for faithful chromosome segregation and how kinetochore malfunction causes various human pathologies.
Keywords: Aneuploidy; Cancer; Cell division; Chromosomal instability; Development; Kinetochore; Microcephaly; Taverne; General Medicine; General Biochemistry,Genetics and Molecular Biology; Journal Article; Review